World Bank Group/World Bank Corporate Scorecards, April 2016 - World Bank Group (World Bank, Washington, DC, 2016)
This pamphlet presents the World Bank Group and World Bank Corporate Scorecards updated with latest data available for Tier 3 (Performance Tier) as of December 31, 2015. Tiers 1 and 2 present data from end of fiscal year 2015. The World Bank Group Corporate Scorecard monitors the implementation of the World Bank Group Strategy. The Scorecard provides an apex view of the results and performance indicators of the three World Bank Group institutions—the World Bank (WB), the International Finance Corporation (IFC), and the Multilateral Investment Guarantee Agency (MIGA). The World Bank Group Corporate Scorecard is complemented by the World Bank Corporate Scorecard as well as the revised IFC and MIGA Scorecards.